2010
DOI: 10.1111/j.1365-277x.2010.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a public health nutrition workforce development intervention for the nutrition and dietetics workforce

Abstract: Mentoring supported service re-orientation and competency development in public health nutrition. The nature of the group learning environment and the role and qualities of the mentor were important elements contributing to the interventions effects. Mentoring circles offer a potentially effective strategy for workforce development in nutrition and dietetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 22 publications
4
50
0
Order By: Relevance
“…There is little research on the mentoring partnerships in Australia; however, research has shown that the mentoring partnership can facilitate lifelong learning through supporting the habit of reflective practice [58]. Palermo et al found that mentor attributes of facilitating trusting relationships and providing effective feedback, were important components of mentoring [59]. This study supports this finding, with dietitians in this study reporting positive relationships and experiences with their mentor, and this positive experience compelled some dietitians to seek ongoing mentoring after the mandatory period was over, throughout their career.…”
Section: Discussionmentioning
confidence: 99%
“…There is little research on the mentoring partnerships in Australia; however, research has shown that the mentoring partnership can facilitate lifelong learning through supporting the habit of reflective practice [58]. Palermo et al found that mentor attributes of facilitating trusting relationships and providing effective feedback, were important components of mentoring [59]. This study supports this finding, with dietitians in this study reporting positive relationships and experiences with their mentor, and this positive experience compelled some dietitians to seek ongoing mentoring after the mandatory period was over, throughout their career.…”
Section: Discussionmentioning
confidence: 99%
“…One study had a controlled non-randomized trial design (16). A total of 18 studies, meanwhile, used a pre–post-intervention evaluation and quasi-experimental design with or without a control group (17, 20, 21, 24, 3749). …”
Section: Analysis Strategymentioning
confidence: 99%
“…A study conducted among advanced-level public health nutritionists in Australia (80) revealed that mentoring, from both peers and senior colleagues, was identified as a significant contributor to competency development. Evidence further indicates that mentoring creates opportunities for networking and access to resources, improves career and personal satisfaction, increases professional and interpersonal skills as well as confidence, and develops reflection for both the mentee and mentor (81) . A mentoring programme could be informal or formal and include one-to-one, group and peer mentoring models.…”
Section: Workforce Preparationmentioning
confidence: 99%